Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14174282
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Repair Classifier Defines Distinct Groups in Hepatocellular Carcinoma

Abstract: DNA repair pathways have been associated with variability in hepatocellular carcinoma (HCC) clinical outcomes, but the mechanism through which DNA repair varies as a function of liver regeneration and other HCC characteristics is poorly understood. We curated a panel of 199 genes representing 15 DNA repair pathways to identify DNA repair expression classes and evaluate their associations with liver features and clinicopathologic variables in The Cancer Genome Atlas (TCGA) HCC study. We identified two groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…Our analysis revealed that the high-risk group was significantly associated with a shorter OS, advanced TNM stage, and higher tumor grade. Moreover, independent prognostic analysis confirmed that the risk score was an independent predictor of OS, this is similar to previous findings that high repair groups tend to be accompanied by a worse prognosis 15 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis revealed that the high-risk group was significantly associated with a shorter OS, advanced TNM stage, and higher tumor grade. Moreover, independent prognostic analysis confirmed that the risk score was an independent predictor of OS, this is similar to previous findings that high repair groups tend to be accompanied by a worse prognosis 15 .…”
Section: Discussionsupporting
confidence: 89%
“…Some DNA damage repair genes (DDRGs) have been employed to forecast the overall survival (OS) of HCC in addition to serum indicators 14 . Recent findings have shown that HCC was categorized into high-repair and low-repair groups based on the expression of DDRGs, and that the high-repair group had a worse prognosis, increased expression of p53 mutation-like genes, and more clinically aggressive features compared to the low-repair group 15 . However, additional research is necessary to determine the exact mechanism by which DDR causes cancer in HCC.…”
Section: Introductionmentioning
confidence: 99%
“… 1 It has been reported that DDR is involved in prognosis, tumour initiation, metastasis and antitumor immune responses. 2 , 3 DDR status has been confirmed to serve as a potential biomarker to predict opposite clinical prognosis of immunotherapy. WHSC1 encodes a SET domain‐containing histone methyltransferase, which could catalyse the di‐methylation of H3K36 to involve in gene transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…DDR pathway has become the target of antitumour drugs 1 . It has been reported that DDR is involved in prognosis, tumour initiation, metastasis and antitumor immune responses 2,3 . DDR status has been confirmed to serve as a potential biomarker to predict opposite clinical prognosis of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Hepatocellular carcinoma (HCC) is a malignancy related to DNA damage and mutagenesis caused by various hepatitis caused by virus, fatty infiltration, and alcoholic liver disease, which leads to carcinogenesis. 29 Some studies have recently reported that DNA repair signaling pathway in HCC cells contributed to worse prognosis [30][31][32][33] ; however, no detailed mechanisms have been reported in this regard. Based on the role of BCL11B in biology, it is reasonable to hypothesize that BCL11B is involved in the clinical course of HCC as it is treated with various DNA-damaging chemotherapy and radiotherapy agents.…”
Section: Introductionmentioning
confidence: 99%